ATP2C2 and DYX1C1 are putative modulators of dyslexia‐related MMR. Issue 11 (18th October 2017) - Müller, Bent; Schaadt, Gesa; Boltze, Johannes; Emmrich, Frank; ,; Skeide, Michael A.; Neef, Nicole E.; Kraft, Indra; Brauer, Jens; Friederici, Angela D.; Kirsten, Holger; Wilcke, Arndt
Abstract: Background: Dyslexia is a specific learning disorder affecting reading and spelling abilities. Its prevalence is ~5% in German‐speaking individuals. Although the etiology of dyslexia largely remains to be determined, comprehensive evidence supports deficient phonological processing as a major contributing factor. An important prerequisite for phonological processing is auditory discrimination and, thus, essential for acquiring reading and spelling skills. The event‐related potential Mismatch Response (MMR) is an indicator for auditory discrimination capabilities with dyslexics showing an altered late component of MMR in response to auditory input. Methods: In this study, we comprehensively analyzed associations of dyslexia‐specific late MMRs with genetic variants previously reported to be associated with dyslexia‐related phenotypes in multiple studies comprising 25 independent single‐nucleotide polymorphisms (SNPs) within 10 genes. Results: First, we demonstrated validity of these SNPs for dyslexia in our sample by showing that additional inclusion of a polygenic risk score improved prediction of impaired writing compared with a model that used MMR alone. Secondly, a multifactorial regression analysis was conducted to uncover the subset of the 25 SNPs that is associated with the dyslexia‐specific late component of MMR. In total, four independent SNPs within DYX1C1 and ATP2C 2 were found to be associated with MMR stronger than expected from multiple testing. To explore potential pathomechanisms, we annotated these variants with functional data including tissue‐specific expression analysis and eQTLs. Conclusion: Our findings corroborate the late component of MMR as a potential endophenotype for dyslexia and support tripartite relationships between dyslexia‐related SNPs, the late component of MMR and dyslexia. Abstract : We analyzed the link between dyslexia‐related SNPs and the auditory discrimination indicator Mismatch Response (MMR). We observed stronger association of these SNPs than expected by chance. We annotated these variants with functional attributes including effects on gene expression levels to get insights into potential pathomechanisms. Our findings corroborate the late component of MMR as potential endophenotype for dyslexia and support tripartite relationships between dyslexia‐related SNPs, the late component of MMR and dyslexia.